Formulasi sucrose-free hard candy dengan suplementasi oleoresin ekstrak cabe jamu (Piper retrofractum Vahl. - Supriyanto Supriyanto; Mojiono Mojiono (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
Hard candy is one of the processed products loved by all groups from children to older people. However, hard candy containing sucrose constituent ingredients can trigger the onset of various diseases, including dental caries. The formulation of free sucrose hard candy with herbal pepper is expected to solve this problem. This study aimed to determine the characteristics of sucrose-free hard candy products from herbal pepper oleoresins. This research began with oleoresin extraction of herbal pepper using the UAE (Ultrasound-Assisted Extraction) method as a source of antioxidants and antibacterials. Oleoresin chili herbal medicine is further used to manufacture free sucrose hard candy formula. The research design used in this study used non-factorial RAL with formula variation treatment to manufacture free sucrose hard candy. The main parameters observed in this study were antioxidant activity and inhibitory power against mutant Streptococcus bacteria. The results showed that the higher oleoresin of herbal pepper can increase the content of antioxidants and antibacterial-free Sucrose Hard Candy. Using xylitol and herbal pepper extract can increase the inhibitory power of mutant Streptococcus bacteria in free sucrose hard candy.